Project-Based Learning Enhances Green Energy Literacy in Indonesian Vocational Education: A Multisite Quasi-Experiment - Maulana Paramaditya Ananta; Muhammad Fadhil Hadziq; Rihlah Nur Aulia; Sofwan Manaf (Jambi Tuah Tengganai, 2026)
Indonesian vocational higher education struggles to equip students with green energy competencies needed for the renewable energy transition. However, evidence on effective project-based models across diverse regional contexts remains scarce. This multisite quasi-experimental study evaluated a Technological-Pedagogical-Content-Knowledge-informed, culturally responsive Project-Based Learning model across three Indonesian cities (Batam, Yogyakarta, Makassar). We assigned 186 engineering students to either 14 weeks of project-based intervention or to conventional instruction, and measured practical competency, conceptual understanding, and digital technology integration. The intervention produced large, consistent effects across all outcomes (Cohen's d = 1.63-1.98), with no significant site-by-condition interaction. Qualitative thematic analysis of 279 reflective journals and six instructor interviews identified contextual relevance, collaborative troubleshooting, teacher technology brokering, and civic orientation as explanatory mechanisms. Despite effect sizes substantially exceeding typical educational technology interventions in low- and middle-income countries, partial assessor blinding and intact class assignment preclude fully causal attribution. The study contributes multisite evidence from a Global South setting, operationalizes TPACK and culturally responsive pedagogy as a combined design logic anchored in Indonesia's tri-pusat tradition, and offers a scalable model linking SDG 4 and SDG 7. Future research requires randomized controlled trials, longitudinal follow-up, cost-effectiveness analysis, and replication in eastern Indonesian provinces.